Subsequent tropical cyclogenesis in the South China Sea induced by the pre-existing tropical cyclone over the western North Pacific: a case study - Wu, Yue; Chan, Kelvin T. F. (Frontiers in Earth Science, 2023)
A new tropical cyclogenesis mechanism in the South China Sea, namely PTC-STC, is proposed. It is discovered that a subsequent tropical cyclone (STC) in the South China Sea can be induced by a pre-existing tropical cyclone (PTC) over the western North Pacific. The observations, reanalysis, and numerical sensitivity experiments suggest that the terrain of the Philippines (especially Luzon) is geographically essential to the tropical cyclogenesis and development of STC, whereas the intensity and track of PTC are conditionally decisive. If the terrain of the Philippines is replaced by sea, no STC forms. The steep mountain range of Luzon provides static blocking effect that can (1) enhance the upward motion; (2) accumulate warm moist air mass from the westerly and PTC; and (3) constrain the advection of vorticity from the PTC. Meanwhile, the northeasterly from the PTC climbs over the terrains, increases the diabatic heating, and warms the proximity in the leeside of the mountains. These processes show that the interactions between the PTC and the terrain of the Philippines could provide favorable dynamic and thermodynamic conditions for the tropical cyclogenesis of STC in the low-to-mid troposphere of the South China Sea. Whereas, if the PTC is too strong, it could move into the South China Sea, suppressing the standalone favorable conditions for the tropical cyclogenesis of STC in the South China Sea.